A comparative UPLC‐Q‐Orbitrap‐MS untargeted metabolomics investigation of different parts of Clausena lansium (Lour.) Skeels. Issue 11 (3rd October 2020) - Fan, Ruiyi; Peng, Cheng; Zhang, Xinxin; Qiu, Diyang; Mao, Genlin; Lu, Yusheng; Zeng, Jiwu
Abstract: In this study, the non‐targeted large‐scale plant metabolomics (UPLC‐Q‐Orbitrap‐MS) was performed for the comparison of chemical profiling of the leaves, barks, flowers, peels, pulps, and seeds of Clausena lansium (Lour.) Skeels (called "wampee"). A total of 364 metabolites were identified, and 62 potential biomarkers were selected by the multivariate statistical analysis. Hierarchical cluster analysis suggested that the selected biomarkers were significant differential metabolites among various parts of wampee. Metabolic pathway analysis showed a significant enrichment of the "Flavone and flavonol synthesis" and "Isoquinoline alkaloid biosynthesis" pathway. This study provides important information for the isolation and identification of functional components from different tissues of wampee and the metabolic biosynthesis pathway elucidation in detail. Abstract : The comparison of chemical profiling of the leaves, barks, flowers, peels, pulps, and seeds of wampee was investigated. This study provides important information for the isolation and identification of functional components from different tissues of wampee and the metabolic biosynthesis pathway elucidation in detail.